The Effect of the Audit Committee and Independent Ownership on the Performance of Insurance Companies Listed on the Indonesia Stock Exchange during the 2019–2024 Period - Rendi Ardika (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the influence of institutional ownership and audit committee characteristics on the financial performance of insurance companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2024. Financial performance is proxied by Return on Equity (ROE). Using a quantitative approach, this study applies panel data regression to a balanced sample of 11 insurance firms, resulting in 66 firm-year observations. Model selection procedures, including the Chow and Hausman tests, indicate that the Fixed Effect Model (FEM) is the most appropriate estimation method. To ensure robustness, data transformation was implemented and heteroskedasticity was examined using the White test. The results show that institutional ownership does not have a statistically significant effect on ROE, whereas the audit committee exhibits a positive and significant influence on financial performance. In addition, joint significance testing confirms that institutional ownership and the audit committee collectively affect ROE. These findings suggest that corporate governance mechanisms operate as an integrated system rather than as isolated controls. The study contributes to the corporate governance literature by providing sector-specific evidence from the insurance industry in an emerging market and offers practical implications for regulators and firm management in strengthening audit committee effectiveness to enhance financial performance.